First report of phthalate acid esters (plasticizers) in blubber of southern right whales (Eubalaena australis) from Península Valdés, Argentina - Luciana Gallo; Melina Paola Michlig; Maria Rosa Repetti; Agustina Donini; Adrian E. Rodriguez; Mariano Sironi; Marcela M. Uhart (Polar Biology, 2026)
Phthalate acid esters (PAEs) are widely used plastic additives that have become ubiquitous contaminants in marine environments. Filter-feeding baleen whales may be exposed to these pollutants through water, prey or ingested plastic debris. While macroplastics have been reported in the gut of a southern right whale (SRW, Eubalaena australis ), exposure to PAEs has not been assessed. Here, we quantified three lipophilic PAEs, dimethyl phthalate (DMP), dibutyl phthalate (DBP), and di-2-ethylhexyl phthalate (DEHP), in the blubber of 13 SRWs (three calves, three juveniles and seven adults) stranded in 2021 at Península Valdés, Argentina. More than 90% of samples contained detectable PAE levels, and 46.2% were above quantification limits. DEHP and DBP were the most prevalent compounds (61.5% and 30.8%, respectively), although the biological significance of the detected concentrations remains uncertain. This is the first report of PAEs in SRW blubber and suggests potential mother-calf transfer, highlighting exposure of Southern Hemisphere mysticetes to plastic-derived chemicals.

Chemical characterization of weathered polyethylene microplastics in marine coastal waters using OPLS-DA technique and ATR FT-IR spectra - Matilda Mali; Rosa Ragone; Valentina Petrelli; Elhussein Mohamed Fouad Mourad Hussein Ahmed; Vito Gallo; Piero Mastrorilli; Maria Michela Dell'Anna (Marine Pollution Bulletin, 2026)

Soil Microbial Diversity and Network Organization Respond to Land Use and Agricultural Inputs Worldwide - Zaki Saati‐Santamaría; Sergio Pérez‐Gorjón; Daniel Abel‐Schaad; Alberto Acedo‐Bécares; Francisca Alba‐Sánchez; Amanda Lucia Alves; Weronika Babinska‐Wensierska; Jorge Ariel Marfetán; Carolina Barroetaveña; Kara Barry; Francisco Beitia; Katerina Biniari; et al. (Global Change Biology, 2026)
Soil microbiomes are critical for ecosystem functioning, yet the global influences of climate and agricultural practices on their diversity and structure remain incompletely characterized. Here we analyzed 1921 soil samples from 33 countries worldwide across diverse biomes to assess how climate gradients and agricultural inputs, including pesticides and fertilizers, shape prokaryotic and fungal communities. We found that microbial diversity peaks at intermediate temperatures and differs markedly between natural and agricultural soils, with agriculture increasing microbial diversity while altering community composition and ecological guilds. Pesticide use selectively reduced bacterial diversity and shifted fungal guilds, decreasing ectomycorrhizal fungi while increasing saprotrophs, whereas fertilization reduced microbial network cohesion, with organic and inorganic fertilizers eliciting distinct community responses. These findings reveal that climatic factors and agricultural management jointly influence soil microbial diversity, community structure, and network connectivity, with implications for soil health and ecosystem resilience in managed landscapes. Overall, our results demonstrate that agricultural practices, including the use of pesticides and both organic and inorganic fertilizers, act as strong ecological filters that reshape soil microbiomes worldwide—enhancing apparent diversity but driving a functional shift toward less mutualistic, more fragmented, and potentially less resilient communities.

Beneficial effect of oat-based postbiotics produced through capsule or free-cell fermentation on lipopolysaccharide activated intestinal cells - Giulia Lentini; Francesca Passannanti; Francesca De Palma; Marianna Gallo; Natasha Petecca; Maria Stefania Spagnuolo; Andrea Budelli; Roberto Nigro; Luisa Cigliano (Food Chemistry, 2026)

A century of research on Azospirillum and still so much to discover - Fabricio Cassán; Guillermo Maroniche; Verónica Massena Reis; Rafael Mazer Etto; Gabriele Bellotti; Gladys Alexandre; Daniela Torres; Sofia Nievas; Anil Kumar Tripathi; Rebeca Perez; Emanuel Maltempi de Souza; Ernesto García Pineda; et al. (Plant and Soil, 2026)

Serum Vitamin E Levels in Multiple Sclerosis: Association with Diagnosis, Cognitive Function, Disability, and Depressive Symptoms - Francesco Bruno; Patrizia Spadafora; Mario Luca Cuconati; Antonio Qualtieri; Ida Veltri; Selene De Benedittis; Beatrice Maria Greco; Annamaria Cerantonio; Luigi Citrigno; Gemma Di Palma; Olivier Gallo; Alberto Montesanto; et al. (Molecular Neurobiology, 2026)
Multiple sclerosis (MS) is a chronic inflammatory and neurodegenerative disease of the central nervous system and the most common neurodegenerative disease in young adults, characterized by motor, sensory, visual, and cognitive impairments. Vitamin E (α-Tocopherol), a fat-soluble antioxidant, may influence cognitive function, disability, and mood in MS. One hundred eighty-four Italian Caucasian MS patients and ninety-four healthy controls were included. Clinical and demographic variables were recorded, and serum vitamin E levels were measured by HPLC. Cognitive function was assessed using the Mini-Mental State Examination (MMSE), disability with the Expanded Disability Status Scale (EDSS), and depressive symptoms with the Hamilton Depression Rating Scale (HDRS). Logistic and linear regression analyses were performed, adjusting for demographic, MS-related, and metabolic confounders. Bonferroni correction was applied. Discriminative ability for clinical cut-offs (MMSE ≤ 24, EDSS ≥ 6, HDRS ≥ 8) was assessed using receiver operating characteristic (ROC) curves. MS patients had significantly lower serum vitamin E levels compared to controls. Lower vitamin E levels were associated with MS diagnosis. In MS patients, higher vitamin E levels were associated with better cognitive performance and lower disability. All associations remained significant after Bonferroni correction in fully adjusted models. No significant relationship was found between vitamin E levels and depressive symptoms. Vitamin E showed good discriminative ability. Serum vitamin E levels showed significant associations with MS diagnosis, cognitive function, and disability, with good discriminative ability. Longitudinal studies are needed to clarify whether low vitamin E levels influence the risk of developing MS, while randomized controlled trials are warranted to determine whether vitamin E supplementation may provide clinical benefits.

Cytogenetic and molecular characterization of an atypical ETP-ALL case with BCL2 dependency: therapeutic implications for Venetoclax use - Francesco Gigliotti; Carolina Brescia; Salvatore Audia; Maria Eugenia Gallo Cantafio; Paola Malatesta; Michelle‑Li Bellisario; Roberta Torcasio; Renato Cantaffa; Eulalia Galea; Rodolfo Iuliano; Giuseppe Viglietto; Francesco Trapasso; et al. (Molecular Biology Reports, 2025)
Background Early T-cell precursor acute lymphoblastic leukemia (ETP-ALL) is a rare, high-risk subtype of T-ALL characterized by distinctive immunophenotypic and genomic features. It is often associated with induction failure and frequent relapses. Despite recent advances in its molecular characterization, the prognosis remains dismal, and effective targeted therapies are limited. Methods and results We report a pediatric, multi-refractory ETP-ALL case with novel cytogenetic alterations, including a 4q deletion and a t(16;18)(q24;q21) translocation. Molecular profiling revealed progressive activation of the BCL2 pathway and disruption of Th17-related immune markers. Ex vivo sensitivity assays performed at different disease stages demonstrated increasing BCL2 dependency. Based on these findings, venetoclax was administered on a compassionate-use basis, resulting in rapid hematologic recovery and a marked reduction in blast percentage. Conclusions This case highlights the role of clonal evolution and immune deregulation in accompanying BCL2 addiction in relapsed ETP-ALL. Altogether, our findings underscore the therapeutic potential of venetoclax in refractory pediatric ETP-ALL cases with progressive BCL2 dependency.

Trace Element Accumulation and Oxidative Stress in Three Populations of the European Eel Anguilla anguilla L. from Southern Italy - Mariacristina Filice; Samira Gallo; Alessia Caferro; Gianni Giglio; Francesco Luigi Leonetti; Concetta Milazzo; Alfonsina Gattuso; Maria Carmela Cerra; Donatella Barca; Emilio Sperone; Sandra Imbrogno (Fishes, 2025)
The European eel (Anguilla anguilla), a catadromous species currently listed as Critically Endangered by the IUCN, is undergoing a severe continental decline. Among the multiple contributing factors, chemical contamination of aquatic environments—particularly by heavy metals—plays a major role. This study analyzed the concentrations of 16 trace elements in the muscle tissue of A. anguilla specimens collected from three ecologically distinct sites in Southern Italy: an estuary (Foce del Crati), a lagoon (Laghi di Gizzeria) and a stream (torrente Raganello). Correlations between trace element accumulation and the onset of oxidative stress were also examined. To assess eel health status, oxidative biomarkers were also analyzed in heart, liver, and gill tissues. Statistical analysis among populations revealed significant differences in the bioaccumulation of 10 of the 16 elements, with Cd and As being of particular concern. No significant correlations were found between these two elements and oxidative biomarkers, but Spearman analysis identified both positive and negative correlations with other elements varying by the site of collection. Oxidative biomarkers also showed site- and tissue-specific variation. In particular, SOD activity was highest in the liver and varied across sites; LPO and protein carbonyl levels were generally lower in eels from the Crati River, although heart values deviated from this trend, highlighting tissue-specific response patterns. These results underscore the complex interplay between chemical contamination and the physiology of the European eel, emphasizing the influence of environmental context in modulating tissue-specific oxidative responses.

Two novel eco-friendly seed dressing nano-antifungals based on pH-responsive dendritic silica nanoparticles coated with chitosan and polydopamine - Maria Paz García-Simarro; María Mondéjar-López; Nuria Genicio; Lourdes Gómez-Gómez; Juan Gallo; Oussama Ahrazem; Manuel Bañobre-López; Enrique Niza (Journal of Environmental Chemical Engineering, 2025)

Correction to: Mapping family farming in brazil’s midwest: assessing socioeconomic and environmental factors for enhancing regional food security - Lucas de Almeida Moura; Caroline de Oliveira Gallo; Francisco Chiaravalloti Neto; Alisson Diego Machado; Marina Maintinguer Norde; Giovanna Garrido; Nadine Marques Nunes Galbes; Aline Martins de Carvalho; Dirce Maria Lobo Marchioni (Food Security, 2025)

Mapping family farming in Brazil’s Midwest: Assessing socioeconomic and environmental factors for enhancing regional food security - Lucas de Almeida Moura; Caroline de Oliveira Gallo; Francisco Chiaravalloti Neto; Alisson Diego Machado; Marina Maintinguer Norde; Giovanna Garrido; Nadine Marques Nunes Galbes; Aline Martins de Carvalho; Dirce Maria Lobo Marchioni (Food Security, 2025)

Microplastics interaction with bisphenol A: Adsorption, desorption, and in vitro biological effects - Astrid Saraceni; Valentina Schiavo; Barbara Mognetti; Erika Cottone; Alberta Trianni; Fabio Beccari; Federico Catalano; Federica Geddo; Giorgio Roberto Merlo; Maria Pia Gallo; Federica Dal Bello; Patrizia Bovolin (Science of The Total Environment, 2025)

Comparative analysis of nutritional and chemical profiles of Tiggiano and Polignano carrots - Maria De Benedictis; Aurelia Scarano; Marco Taurino; Maria Tufariello; Lorenzo Palombi; Federica Blando; Massimiliano Renna; Angelo Santino; Antonia Gallo (Food Bioscience, 2025)

Evaluation of SARS-CoV-2 antibody detection methods for wild Cervidae - Joshua Hewitt; Grete Wilson-Henjum; Jeffrey C. Chandler; Aaron T. Phillips; Diego G. Diel; W. David Walter; Alec Baker; Jennifer Høy-Petersen; Guillaume Bastille-Rousseau; Tadao Kishimoto; George Wittemyer; Jeremy Alder; et al. (Preventive Veterinary Medicine, 2025)

Diet composition and apparent digestibility in giant anteaters (Myrmecophaga tridactyla) kept under human care - Thaís Moreira Gentini; Fernanda Mara Macedo Aragão Pereira; Lucas Batista da Silva; Maria Fernanda Hussni; Danyele Karoline Avante Mangueira; Carolyne Assis Eigerheer Pinke Testa; Caroline de Cássia Gallo; Lucas Carneiro; Paulo Roberto de Lima Meirelles; Priscylla Tatiana Chalfun Guimarães Okamoto; Ellen Sue Dierenfield; Alessandra Melchert (Veterinary Research Communications, 2025)

Dynamic Changes in Oxidative Stress and Epigenetic Modifications in the Ventral Mesencephalon and Striatum of MPTP-Treated Mice: Implications for Parkinson's Disease Pathogenesis - Pablo Gallo-Soljancic; Maria Egle De Stefano; Ana-Maria Gonzalez-Cuello; Emiliano Fernandez-Villalba; Lode Godderis; Maria Trinidad Herrero (Neurotoxicity Research, 2025)
This study investigates the effects of an acute 1-metil 4-fenil 1,2,3,6-tetraidro-piridina (MPTP) treatment, a known inducer of parkinsonism, on oxidative stress and epigenetic changes in the mouse ventral midbrain (VM) and striatum. Key markers were analyzed at 4, 8, 24, and 48 h post-injections: the hydroxylated form of the purine guanine (8-hydroxy-2'-deoxyguanosine; 8-OHdG), a marker of oxidative stress; the methylated form of cytosine (5-methylcytosine; 5-mC), associated with gene silencing; the hydroxy methylated form of cytosine (5-hydroxymethylcytosine; 5-hmC), involved in demethylation and gene regulation. The results showed a pronounced decrease in 8-OHdG levels in the VM, suggesting a rapid oxidative stress response, whereas the striatum exhibited a less pronounced response, reflecting regional differences in oxidative stress vulnerability DNA methylation patterns revealed complex and biphasic changes in 5-mC levels in the VM, contrasted with a less pronounced response in the striatum, suggesting disrupted methylation homeostasis and regional epigenetic variability. MPTP treatment also significantly reduced in 5-hmC levels in the VM, pointing to impaired active DNA demethylation and compromised epigenetic flexibility. In contrast, the striatum maintained consistently high 5-hmC levels, reflecting compensatory hydroxymethylation mechanisms specific to this region. These findings highlight pronounced regional differences in oxidative stress vulnerability and epigenetic regulation, with the VM showing heightened sensitivity to oxidative damage and impaired epigenetic flexibility. This underscores the importance of understanding the role of oxidative and epigenetic mechanisms in Parkinson’s disease pathophysiology, The changes pave the way for novel therapeutic strategies targeting oxidative DNA damage and epigenetic homeostasis.

The effects of enriched biochar and zeolite and treated wastewater irrigation on soil fertility and tomato growth - Sara Paliaga; Sofia Maria Muscarella; Rosa Alduina; Luigi Badalucco; Pedro Tomás Bulacio Fischer; Ylenia Di Leto; Giuseppe Gallo; Giorgio Mannina; Vito Armando Laudicina (Journal of Environmental Management, 2025)

Antidiabetic potential of vanadium complexes combined with olive leaf extracts: a viable approach to reduce metal toxicity - Daniele Sanna; Angela Fadda; Milena Casula; Grazia Palomba; Maria Cristina Sini; Maria Colombino; Carla Rozzo; Giuseppe Palmieri; Carmela Gallo; Dalila Carbone; Laura Siracusa; Luana Pulvirenti; et al. (BioMetals, 2025)
Vanadium compounds are known for their antidiabetic properties due to their ability to interfere with numerous mechanisms that lead to the decrease of blood glucose levels. Although some of these compounds have reached clinical trials and have the advantage of being orally administrable, no vanadium-containing drugs are currently available on the market, primarily due to the high doses required, which can lead intestinal and renal problems in case of long-term treatments. In this study, plant extracts obtained from olive leaves ( Olea europaea L.) were combined with vanadium complexes with established antidiabetic activity with the aim of reducing their metal toxicity and, at the same time, amplifying their hypoglycemic action. The extracts were characterized by chromatographic and spectroscopic methods showing a composition rich in polyphenols and a high antioxidant activity. Formulations containing a vanadium complex (bis(maltolato)oxidovanadium(IV), BMOV, or bis(picolinato)oxidovanadium(IV), BPOV) mixed with different amount of olive leaves extract were tested in vitro to evaluate intestinal toxicity and hypoglycemic activity. The results demonstrated that the plant extracts are generally non-toxic toward human colon fibroblast in the whole range of tested concentrations and some of them are particularly effective in reducing the toxicity of the two vanadium compounds. Further in vitro tests conducted on differentiated human adipocyte cell lines revealed a significant increase in glucose uptake following treatment with the mixed formulations, compared to the effect of the individual components, indicating a synergistic effect. Immunocytochemical assays suggested that the translocation of GLUT4 transporter can be involved in the mechanism of action.

New lithostrotian specimens (Neosauropoda: Titanosauria) from the Mato Grosso State (western Brazil) and comments about tail injuries in sauropod dinosaurs - Letícia Lacerda; Kamila L.N. Bandeira; Bruno A. Navarro; Maria L.P. Bertolossi; Valéria Gallo; Rafael C. da Silva; Diogenes de A. Campos; Alexander W.A. Kellner (Journal of South American Earth Sciences, 2025)

Resource recovery from wastewater treatment: Effects of water reuse and slow-release fertilizers on faba bean within Palermo University (Italy) case study - Sara Paliaga; Sofia Maria Muscarella; Rosa Alduina; Luigi Badalucco; Pedro Tomás Bulacio Fischer; Ylenia Di Leto; Giuseppe Gallo; Raimondo Gaglio; Antonio Mineo; Vito Armando Laudicina; Giorgio Mannina (Journal of Environmental Management, 2025)

Detection of antibacterial peptides in artisanal rennet and evaluation of their antibacterial activity - Angela Michela Immacolata Montone; Sara Elsa Aita; Federico Capuano; Angelo Citro; Alessandra Esposito; Alfonso Gallo; Morena Nappa; Enrico Taglioni; Carmela Maria Montone (International Dairy Journal, 2025)

Methotrexate for osteoarthritis: a systematic review meta-analysis of randomized controlled trials - Ivo Queiroz; Túlio Pimentel; Mariano Gallo Ruelas; Arthur Henrique Tavares; Lucas M. Barbosa; Maria L. R. Defante; Giovanna N. Leandro; Arthur Ribeiro Monteiro; Fernando Nunes Pimentel (Inflammopharmacology, 2025)

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

In vitro study of the UV-filter homosalate effects on rat and human thyroid cells - Francesca Coperchini; Alessia Greco; Marsida Teliti; Marco Denegri; Laura Croce; Benedetto Calì; Maria Gallo; Giovanni Arpa; Spyridon Chytiris; Flavia Magri; Mario Rotondi (Environmental Pollution, 2024)

Factors influencing the bioactivity of natural matrices: The case of osmolarity-dependent modulation of cell viability by different dilutions of camel urines - Carlos Iglesias Pastrana; Maria Noemi Sgobba; Francisco Javier Navas González; Juan Vicente Delgado Bermejo; Ciro Leonardo Pierri; Giovanni Lentini; Biagia Musio; Taher Kamal Sayed Osman; Vito Gallo; Iola F. Duarte; Lorenzo Guerra; Elena Ciani (Research in Veterinary Science, 2024)

Evaluating the effectiveness of DNA-based methods to detect mislabelling and adulteration of chestnut honey - Teresa Maria Rosaria Regina; Federica Gallo (Food Bioscience, 2024)

Selection of Genipa americana L. seed trees by genetic divergence in fruit, seeds, and seedlings - Raquel Elvira Cola; Maria da Penha Moreira Gonçalves; Maria Inês Sucupira Maciel; Lidiana Nayara Ralph; Larissa Santiago Ritt Ordonho; Ricardo Gallo (Genetic Resources and Crop Evolution, 2024)

Water reuse of treated domestic wastewater in agriculture: Effects on tomato plants, soil nutrient availability and microbial community structure - Sofia Maria Muscarella; Rosa Alduina; Luigi Badalucco; Fanny Claire Capri; Ylenia Di Leto; Giuseppe Gallo; Vito Armando Laudicina; Sara Paliaga; Giorgio Mannina (Science of The Total Environment, 2024)

Reproductive toxicity assessment of cellulose nanofibers, citric acid, and branched polyethylenimine in sea urchins: Eco-design of nanostructured cellulose sponge framework (Part B) - Maria Consiglia Esposito; Laura Riva; Gian Luigi Russo; Carlo Punta; Ilaria Corsi; Elisabetta Tosti; Alessandra Gallo (Environmental Pollution, 2024)

Nanostructured cellulose sponge engineered for marine environmental remediation: Eco-safety assessment of its leachate on sea urchin reproduction (Part A) - Maria Consiglia Esposito; Gian Luigi Russo; Laura Riva; Carlo Punta; Ilaria Corsi; Elisabetta Tosti; Alessandra Gallo (Environmental Pollution, 2023)

A sustainable approach to enhance heavy hydrocarbons removal in landfarming treatment - Camilla Di Marcantonio; Agostina Chiavola; Alessandra Noce; Elisabetta Straccamore; Andrea Giannuzzi; Jacopo Jirillo; Francesco Gallo; Maria Rosaria Boni (Biodegradation, 2023)
The present study aimed to evaluate the best strategy to enhance the degradation rate of heavy petroleum hydrocarbons (HPH) contaminated soil in a landfarming plant. Samples of real contaminated soil, further spiked with HPH, were treated in mesocosm reactors simulating the landfarming system. One reactor was operated without any modification compared to the real landfarming plant. The other three reactors were operated with different strategies to improve the removal rate: biostimulation (BS) through the addition of nitrogen and phosphorus; bioaugmentation (BA) with the inoculation of sludge produced in the treatment of the process water from the oil re-fining plant of the same industrial area; combination of biostimulation and bioaugmentation (BAS). The biostimulation (BS) was the most effective strategy, leading to a reduction of the remediation time by 35% as compared to the traditional treatment. Bioaugmentation (BA) also provided positive effects leading to a reduction of the remediation time by 24%; its performance improved further when the addition of sludge was combined with the increase of phosphorous (BAS). Therefore, the key tool was represented by the phosphorous availability, whereas the application of sludge was most useful to provide waste with a new possibility of reuse, thus fulfilling the principles of the circular economy. The final characterization showed that the treated soil was suitable for reuse in industrial areas according to the legislation in force.

Assessment on the effect of erythromycin on the microbiome of a bioslurry pilot plant for contaminated sediment bioprocessing - Gaetano Di Bella; Lucia Lumia; Alberto Sutera; Graziella Rabbeni; Maria Gabriella Giustra; Giuseppe Gallo (Bioresource Technology Reports, 2023)

New approaches concerning the testis of Astyanax lacustris (Characidae): immunohistochemical studies - Fabiano Gonçalves Costa; Chayrra Chehade Gomes; Mateus Contar Adolfi; Mayra Costa da Cruz Gallo de Carvalho; Marco Antônio Zanoni; Fábio Rodrigues Ferreira Seiva; Maria Inês Borella (Fish Physiology and Biochemistry, 2023)

Exiguobacterium sp. as a bioinoculant for plant-growth promotion and Selenium biofortification strategies in horticultural plants - Jorge A. Marfetán; Ana L. Gallo; Maria E. Farias; Maria L. Vélez; Micaela Pescuma; Omar F. Ordoñez (World Journal of Microbiology and Biotechnology, 2023)

Volatile and chemical profiles of Bombino sparkling wines produced with autochthonous yeast strains - Maria Tufariello; Lorenzo Palombi; Antonino Rizzuti; Biagia Musio; Vittorio Capozzi; Vito Gallo; Piero Mastrorilli; Francesco Grieco (Food Control, 2023)

Otoliths of marine fishes record evidence of low oxygen, temperature and pH conditions of deep Oxygen Minimum Zones - Leticia Maria Cavole; Karin E. Limburg; Natalya D. Gallo; Anne Gro Vea Salvanes; Arturo Ramírez-Valdez; Lisa A. Levin; Octavio Aburto Oropeza; Andreas Hertwig; Ming-Chang Liu; Kevin D. McKeegan (Deep Sea Research Part I: Oceanographic Research Papers, 2023)

MASTREE+: Time‐series of plant reproductive effort from six continents - Andrew Hacket‐Pain; Jessie J. Foest; Ian S. Pearse; Jalene M. LaMontagne; Walter D. Koenig; Giorgio Vacchiano; Michał Bogdziewicz; Thomas Caignard; Paulina Celebias; Joep van Dormolen; Marcos Fernández‐Martínez; Jose V. Moris; et al. (Global Change Biology, 2022)
Significant gaps remain in understanding the response of plant reproduction to environmental change. This is partly because measuring reproduction in long‐lived plants requires direct observation over many years and such datasets have rarely been made publicly available. Here we introduce MASTREE+, a data set that collates reproductive time‐series data from across the globe and makes these data freely available to the community. MASTREE+ includes 73,828 georeferenced observations of annual reproduction (e.g. seed and fruit counts) in perennial plant populations worldwide. These observations consist of 5971 population‐level time‐series from 974 species in 66 countries. The mean and median time‐series length is 12.4 and 10 years respectively, and the data set includes 1122 series that extend over at least two decades (≥20 years of observations). For a subset of well‐studied species, MASTREE+ includes extensive replication of time‐series across geographical and climatic gradients. Here we describe the open‐access data set, available as a.csv file, and we introduce an associated web‐based app for data exploration. MASTREE+ will provide the basis for improved understanding of the response of long‐lived plant reproduction to environmental change. Additionally, MASTREE+ will enable investigation of the ecology and evolution of reproductive strategies in perennial plants, and the role of plant reproduction as a driver of ecosystem dynamics.

Efficacy of high-intensity interval- or continuous aerobic-training on insulin resistance and muscle function in adults with metabolic syndrome: a clinical trial - Jaime Gallo-Villegas; Leonardo A. Castro-Valencia; Laura Pérez; Daniel Restrepo; Oscar Guerrero; Sergio Cardona; Yeliana L. Sánchez; Manuela Yepes-Calderón; Luis H. Valbuena; Miguel Peña; Andrés F. Milán; Maria C. Trillos-Almanza; et al. (European Journal of Applied Physiology, 2022)

Corneal transplant during COVID-19 pandemic: the Italian Eye Bank national report - Francesco Aiello; Federico Genzano Besso; Giulio Pocobelli; Gabriele Gallo Afflitto; Rossella Anna Maria Colabelli Gisoldi; Carlo Nucci; Diego Ponzin; Paola Bonci; Giuseppe Calabrò; Roberto Ceccuzzi; Massimiliano Corneli; Germano Genitti; et al. (Cell and Tissue Banking, 2021)
To investigate the impact of Coronavirus Disease-2019 lockdown on the Italian Eye Bank organization. In this national retrospective, multicentric, cohort study, data from the Italian Eye Bank during both the lockdown and the first month after the lockdown period were retrieved. We compared the Italian Eye Bank metrics with the same timeframe of 2019 and 2018. Data from 13 out of 13 (100%) Italian Eye Banks were included in the analysis. A statistically significant reduction in the number of donor corneas retrieved in 2020 was found as compared to the same period in 2019 and in 2018, respectively (2020 = 1284; 2019 = 3088; 2018 = 3221; ANOVA: p < 0.0001). Only 534 corneas have been distributed by Eye Banks during the COVID-19-lockdown period (2020 = 534; 2019 = 1220; 2018 = 1237. ANOVA: p < 0.0001). Similarly, the number of wasted corneas due to postponed or cancelled surgeries was 421, resulting in a considerable increase as compared to the previous 2 years (2020 = 421; 2019 = 67; 2018 = 84; ANOVA: p = 0.0035). Overall, 45 donor corneas were rejected in accordance with the guidance of the Italian National Health Institute Italian National Transplant Centre (CNT). SARS-CoV-2 pandemic has profoundly affected every social and medical field, including the Eye Bank procurement and distribution programs. The current data collected from all the Italian Eye Banks highlights the present and the forthcoming difficulties that the Eye Bank community is going to experience, as for the ongoing pandemic.

Concentrations of trace elements in tissues of loggerhead turtles (Caretta caretta) from the Tyrrhenian and the Ionian coastlines (Calabria, Italy) - Silvia Canzanella; Amalia Danese; Maria Mandato; Giuseppe Lucifora; Caterina Riverso; Giovanni Federico; Pasquale Gallo; Mauro Esposito (Environmental Science and Pollution Research, 2021)

Coping strategies in relapsing–remitting multiple sclerosis non-depressed patients and their associations with disease activity - Gabriella Santangelo; Marida Della Corte; Maddalena Sparaco; Giuseppina Miele; Federica Garramone; Maria Cropano; Sabrina Esposito; Luigi Lavorgna; Antonio Gallo; Gioacchino Tedeschi; Simona Bonavita (Acta Neurologica Belgica, 2021)

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Sperm Motility Impairment in Free Spawning Invertebrates Under Near-Future Level of Ocean Acidification: Uncovering the Mechanism - Maria Consiglia Esposito; Raffaele Boni; Alessia Cuccaro; Elisabetta Tosti; Alessandra Gallo (Frontiers in Marine Science, 2020)

Preservation of vitamins content in Cuccìa using an innovative method of processing - Rosaria Bognanni; Giulia Gallo; Vita Di Stefano; Maria Grazia Melilli (Natural Product Research, 2020)

Effects of Histone Deacetylase Inhibitors on the Development of Epilepsy and Psychiatric Comorbidity in WAG/Rij Rats - Rita Citraro; Antonio Leo; Carmen De Caro; Valentina Nesci; Maria E. Gallo Cantafio; Nicola Amodio; Giuseppina Mattace Raso; Adriano Lama; Roberto Russo; Antonio Calignano; Martina Tallarico; Emilio Russo; et al. (Molecular Neurobiology, 2020)

A method to determine BPA, BPB, and BPF levels in fruit juices by liquid chromatography coupled to tandem mass spectrometry - Pasquale Gallo; Ilaria Di Marco Pisciottano; Margherita Fattore; Maria Grazia Rimoli; Serenella Seccia; Stefania Albrizio (Food Additives & Contaminants: Part A, 2019)

An integrated proteomic and metabolomic study to evaluate the effect of nucleus-cytoplasm interaction in a diploid citrus cybrid between sweet orange and lemon - Teresa Faddetta; Loredana Abbate; Giovanni Renzone; Antonio Palumbo Piccionello; Antonella Maggio; Elisabetta Oddo; Andrea Scaloni; Anna Maria Puglia; Giuseppe Gallo; Francesco Carimi; Sergio Fatta Del Bosco; Francesco Mercati (Plant Molecular Biology, 2018)

Developing and validating microsatellite markers in elephant grass (Pennisetum purpureum S.) - Yolanda López; Aleksey Kurashev; Christine Chase; Maria Gallo; Lynn Sollenberger; Fredy Altpeter; Jianping Wang (Euphytica, 2018)

Is there correlation between photophobia and troglomorphism in Neotropical cave millipedes (Spirostreptida, Pseudonannolenidae)? - Jéssica Scaglione Gallo; Maria Elina Bichuette (Zoomorphology, 2018)

The seed endosphere of Anadenanthera colubrina is inhabited by a complex microbiota, including Methylobacteriumspp. and Staphylococcus spp. with potential plant-growth promoting activities - Pasquale Alibrandi; Massimiliano Cardinale; MD Mahafizur Rahman; Francesco Strati; Paolo Ciná; Marta L. de Viana; Eugenia M. Giamminola; Giuseppe Gallo; Sylvia Schnell; Carlotta De Filippo; Mirella Ciaccio; Anna Maria Puglia (Plant and Soil, 2018)

Analysis of a non-nodulating Arachis hypogaea L. Whole-Root Proteome Identifies Changes Associated with Host-Rhizobia Interaction - Brad W. Porter; Maria Gallo (Tropical Plant Biology, 2017)

In planta production and characterization of a hyperthermostable GH10 xylanase in transgenic sugarcane - Jae Yoon Kim; Guang Nong; John D. Rice; Maria Gallo; James F. Preston; Fredy Altpeter (Plant Molecular Biology, 2017)

Idiopathic hypertrophic pachymeningitis: an autoimmune IgG4-related disease - Armando De Virgilio; Marco de Vincentiis; Maurizio Inghilleri; Giovanni Fabrini; Michela Conte; Andrea Gallo; Maria Ida Rizzo; Antonio Greco (Immunologic Research, 2017)

Glaucoma: recent advances in the involvement of autoimmunity - Maria Ida Rizzo; Antonio Greco; Armando De Virgilio; Andrea Gallo; Luciano Taverniti; Massimo Fusconi; Michela Conte; Giulio Pagliuca; Rosaria Turchetta; Marco de Vincentiis (Immunologic Research, 2017)

Direct organogenesis from cotyledonary node explants suitable for Agrobacterium-mediated transformation in peanut (Arachis hypogaea L.) - Yih-Feng Hsieh; Mukesh Jain; Jianping Wang; Maria Gallo (Plant Cell, Tissue and Organ Culture (PCTOC), 2017)

Properties and Mechanobiological Behavior of Bovine Nasal Septum Cartilage - Maria Rita Correro-Shahgaldian; Jasmin Introvigne; Chafik Ghayor; Franz E. Weber; Luigi M. Gallo; Vera Colombo (Annals of Biomedical Engineering, 2016)

Polysaccharide-based silver nanoparticles synthesized by Klebsiella oxytoca DSM 29614 cause DNA fragmentation in E. coli cells - Franco Baldi; Salvatore Daniele; Michele Gallo; Stefano Paganelli; Dario Battistel; Oreste Piccolo; Claudia Faleri; Anna Maria Puglia; Giuseppe Gallo (BioMetals, 2016)

Molecular marker development from transcript sequences and germplasm evaluation for cultivated peanut (Arachis hypogaea L.) - Ze Peng; Maria Gallo; Barry L. Tillman; Diane Rowland; Jianping Wang (Molecular Genetics and Genomics, 2016)

Invasive Populations of Elephantgrass Differ in Morphological and Growth Characteristics from Clones Selected for Biomass Production - Lynn E. Sollenberger; Kenneth R. Woodard; João M. B. Vendramini; John E. Erickson; Kenneth A. Langeland; M. Kimberly Mullenix; Chaein Na; Miguel S. Castillo; Maria Gallo; Christine D. Chase; Yolanda López (BioEnergy Research, 2014)

PCR detection of Neospora caninum in water buffalo foetal tissues - Clementina Auriemma; Maria Lucibelli; Giorgia Borriello; Esterina Carlo; Alessandra Martucciello; Lorena Schiavo; Amalia Gallo; Francesca Bove; Federica Corrado; Santa Girardi; Maria Amoroso; Barbara Ďegli Uberti; et al. (Acta Parasitologica, 2014)
The seroprevalence of Neospora caninum was surveyed by an ELISA kit on two water buffalo herds of Southern Italy. Seropositive samples were detected in 47% and 59% of individuals, respectively, thus indicating high level of exposure to the parasite even if the possibility of vertical transmission cannot be excluded. Tissue samples collected from three aborted fetuses from the same herds were investigated for N. caninum presence by PCR assays targeting the 18S and the Nc5 DNA sequences, respectively. Both methods have shown the presence of N. caninum DNA in heart and brain. Sequencing of the Nc5 genomic DNA confirmed the presence of N. caninum in the samples; phylogenetic analysis of the obtained sequences showed high homology among the Neospora recovered from different samples. The present study suggests an important role of N. caninum as a possible abortive agent for water buffaloes.

Comparative analysis of direct plant regeneration from immature leaf whorl and floral explants for three elite US sugarcane (Saccharum spp. hybrids) genotypes - Sunil Joshi; Mukesh Jain; Barry L. Tillman; Fredy Altpeter; Maria Gallo (In Vitro Cellular & Developmental Biology - Plant, 2013)

Application of Abscisic Acid (S-ABA) to ‘Crimson Seedless’ Grape Berries in a Mediterranean Climate: Effects on Color, Chemical Characteristics, Metabolic Profile, and S-ABA Concentration - Giuseppe Ferrara; Andrea Mazzeo; Angela Maria Stella Matarrese; Carmela Pacucci; Andrea Pacifico; Giuseppe Gambacorta; Michele Faccia; Antonio Trani; Vito Gallo; Isabella Cafagna; Piero Mastrorilli (Journal of Plant Growth Regulation, 2013)

Anthropometric characteristics and risk of lymphoid and myeloid leukemia in the European Prospective Investigation into Cancer and Nutrition (EPIC) - Fatemeh Saberi Hosnijeh; Isabelle Romieu; Valentina Gallo; Elio Riboli; Anne Tjønneland; Jytte Halkjær; Guy Fagherazzi; Françoise Clavel-Chapelon; Laure Dossus; Annie Lukanova; Rudolf Kaaks; Antonia Trichopoulou; et al. (Cancer Causes & Control, 2013)

Comparison of procedures for DNA coating of micro-carriers in the transient and stable biolistic transformation of sugarcane - Yuan Xiong; JeHyeong Jung; Qianchun Zeng; Maria Gallo; Fredy Altpeter (Plant Cell, Tissue and Organ Culture (PCTOC), 2013)

In vitro induction of tetraploids in Arachis paraguariensis - Olubunmi Aina; Kenneth Quesenberry; Maria Gallo (Plant Cell, Tissue and Organ Culture (PCTOC), 2012)

Comparison of direct and indirect embryogenesis protocols, biolistic gene transfer and selection parameters for efficient genetic transformation of sugarcane - Yogesh Taparia; Maria Gallo; Fredy Altpeter (Plant Cell, Tissue and Organ Culture (PCTOC), 2012)

Analysis of transgene integration and expression following biolistic transfer of different quantities of minimal expression cassette into sugarcane (Saccharum spp. hybrids) - Jae Yoon Kim; Maria Gallo; Fredy Altpeter (Plant Cell, Tissue and Organ Culture (PCTOC), 2012)

Expansion of a direct shoot organogenesis system in peanut (Arachis hypogaea L.) to include US cultivars - Scott P. Burns; Maria Gallo; Barry L. Tillman (In Vitro Cellular & Developmental Biology - Plant, 2012)

Rapid production of transgenic sugarcane with the introduction of simple loci following biolistic transfer of a minimal expression cassette and direct embryogenesis - Yogesh Taparia; Walid M. Fouad; Maria Gallo; Fredy Altpeter (In Vitro Cellular & Developmental Biology - Plant, 2012)

Comparative assessment of variation in the USA Arachis pintoi (Krap. and Greg.) germplasm collection using RAPD profiling and tissue culture regeneration ability - Marcelo Ayres Carvalho; Kenneth H. Quesenberry; Maria Gallo (Plant Systematics and Evolution, 2010)

Satellite cell ablation attenuates short-term fast-to-slow fibre type transformations in rat fast-twitch skeletal muscle - Karen J. B. Martins; Gordon K. Murdoch; Yang Shu; R. Luke W. Harris; Maria Gallo; Walter T. Dixon; George R. Foxcroft; Tessa Gordon; Charles T. Putman (Pflügers Archiv - European Journal of Physiology, 2009)

Official Surveillance of Hepatitis A Virus: Description of an HAV Detection Method in Shellfish - Laura Serracca; Francesca Gallo; Irene Rossini; Alessandro Benedetto; Daniela Lacerenza; Maria Rita Callipo; Milena Monnier; Maria Goria (Food and Environmental Virology, 2009)

The effect of auxin type and cytokinin concentration on callus induction and plant regeneration frequency from immature inflorescence segments of seashore paspalum (Paspalum vaginatum Swartz) - Isaac Neibaur; Maria Gallo; Fredy Altpeter (In Vitro Cellular & Developmental Biology - Plant, 2008)

Track analysis of the marine palaeofauna from the Turonian (Late Cretaceous) - Valéria Gallo; Mauro J. Cavalcanti; Hilda Maria Andrade da Silva (Journal of Biogeography, 2007)
Aim To analyse the worldwide distribution patterns of Turonian marine biotas using a panbiogeographical approach. Location Turonian localities of southern and north‐eastern Brazil, Mexico, Canada, central Europe, England and Morocco. Method Panbiogeographical track analysis. Results Nine generalized tracks and six nodes were found. The generalized tracks comprise two vicariant track patterns (one northern and one mid‐southern) across the Atlantic. Main conclusions The generalized tracks show clearly two separate marine biotas, which were associated with the proto‐South Atlantic and the proto‐North Atlantic oceans. These generalized tracks, as well as the two vicariant track clusters between the north and south Atlantic, are identified by vicariant relationships shared by most of the taxa analysed, and illustrate the final break up of the Gondwana and Laurasia supercontinents and the consequences of vicariant events for the biogeography of the Atlantic Ocean.

Prospecting the utility of a PMI/mannose selection system for the recovery of transgenic sugarcane (Saccharum spp. hybrid) plants - Mukesh Jain; Kudithipudi Chengalrayan; Ahmed Abouzid; Maria Gallo (Plant Cell Reports, 2007)

2n Gamete formation in the genus Brachiaria (Poaceae: Paniceae) - Patrícia Helena Gallo; Pamela Lonardoni Micheletti; Kellen Regina Boldrini; Claudicéia Risso-Pascotto; Maria Suely Pagliarini; Cacilda Borges do Valle (Euphytica, 2007)

Effects of long-term creatine feeding and running on isometric functional measures and myosin heavy chain content of rat skeletal muscles - Maria Gallo; Tessa Gordon; Daniel Syrotuik; Yang Shu; Neil Tyreman; Ian MacLean; Zoltan Kenwell; Charles T. Putman (Pflügers Archiv - European Journal of Physiology, 2006)

Chromosomal and phylogenetic context for conglutin genes in Arachis based on genomic sequence - M. Laura Ramos; Geraldine Fleming; Ye Chu; Yukio Akiyama; Maria Gallo; Peggy Ozias-Akins (Molecular Genetics and Genomics, 2006)

In vitro propagation of Notocactus magnificus - Lígia Aíra de Medeiros; Roberval Cássia Salvador de Ribeiro; Luiz Antônio Gallo; Enio Tiago de Oliveira; Maria Esmeralda Soares Payão Demattê (Plant Cell, Tissue and Organ Culture (PCTOC), 2006)

Regulation of cardiac calcium current by NO and cGMP-modulating agents - Maria Pia Gallo; Daniela Malan; Ivano Bedendi; Cinzia Biasin; Giuseppe Alloatti; Renzo Cesare Levi (Pflügers Archiv - European Journal of Physiology, 2001)

Airborne fungal spores in dust present in archives: pProposal for a detection method, new for archival materials - Oriana Maggi; Anna Maria Persiani; Fausta Gallo; Paola Valenti; Giovanna Pasquariello; Maria Carla Sclocchi; Mauro Scorrano (Aerobiologia, 2000)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)